Hubungan Penyakit Komorbid dengan Keberhasilan Terapi Fibrinolitik pada Pasien STEMI di Rumah Sakit Umum dr. Fauziah Bireuen - Ulfa Zahara; Aulia Mustika; Nanda Nanda (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
ST-Elevation Myocardial Infarction (STEMI) is one of the manifestations of acute coronary syndrome (ACS) and is a leading cause of disability and death worldwide. The mortality rate for STEMI is reported to reach 6%–14% of all ACS deaths. Reperfusion therapy is the primary treatment, with fibrinolytics an important option, especially in healthcare facilities that do not have the capacity to perform primary Percutaneous Coronary Intervention (PCI) in less than 12 hours. The success of fibrinolytics is influenced by various risk factors, such as hypertension, dyslipidemia, diabetes mellitus, a history of heart disease, and the duration of the attack. This study aims to determine the relationship between these factors and the success rate of fibrinolytics in STEMI patients. This study used a retrospective descriptive design with a cross-sectional method. The sampling technique used total sampling of patients diagnosed with STEMI and receiving fibrinolytic therapy according to inclusion and exclusion criteria at Dr. Fauziah Hospital. Statistical analysis was performed using the Chi-Square correlation test to assess the relationship between clinical variables and fibrinolytic success. The results showed no significant association between hyperglycemia (p = 0.823), hypertension (p = 0.240), or a history of heart disease (p = 0.704) and fibrinolytic success. Similarly, the onset of stroke variable did not show a significant association with reperfusion outcomes. In conclusion, classic risk factors such as hyperglycemia, hypertension, and a history of heart disease were not associated with fibrinolytic success in STEMI patients at Dr. Fauziah Hospital. These results suggest that fibrinolytic success is likely influenced by other factors, such as timing of drug administration, protocol adherence, and individual variation in response to therapy. Further research with a larger sample size and a prospective design is recommended to strengthen these findings.